LATERAL PEG-SHAPED INCISIVE AESTHETIC TREATMENT WITH INDIRECT VENEER RESTORATION USING CERAMO POLYMER RESTORATION - Azkya Nawawi; Nusantari Inda Suzan; Aprilia Adenan; Rasmi Rikmasari (Fakultas Kedokteran Gigi Unjani, 2021)
Peg shape is one of the abnormalities of dental anatomy, i.e. tooth size is smaller than average and tapered shape. These peg-shaped teeth are often found in the maxillary lateral incisors and third molars. The form on the lateral incisor often causes aesthetic problems because of its anterior position. One of the treatments for peg-shaped teeth is Veneer. Case report: 26 years old woman had a peg-shaped shape on both lateral incisors. Indirect veneer aesthetic treatment was performed using Ceramage to correct the form and cover the diastema to achieve better aesthetics. Wax-up is done to see the suitability of the shape and proportion of the Veneer. Patients get a visual picture of the expected treatment results. The treatment results in Ceramage gave an excellent condition in improving the shape of the Peg-shaped incisor. The veneer colour resembles natural teeth, and the patient is satisfied with the treatment results. Ceramage can be used as a treatment option for anterior teeth with deformities. Ceramage Veneer is an alternative that can be done to improve the aesthetic appearance at a more economical cost for anterior teeth. DOI : 10.54052/jhds.v1n2.p121-130